2020
DOI: 10.1109/access.2020.2986797
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitive Triple-Band Rectifier for Energy Harvesting Applications

Abstract: This paper presents a novel sensitive triple-band power rectifier for RF energy harvesting systems. The proposed rectifier can simultaneously harvest RF energy from GSM-900, GSM-1800, and Wi-Fi-2450 bands at relatively low and medium ambient power densities. Previously, a few multi-band rectennas have been reached a stable conversion efficiency overall frequency bands of interest because of the nonlinearity and the distinct input impedance of the rectifying circuit at these frequencies. The originality of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 22 publications
(24 reference statements)
0
26
0
2
Order By: Relevance
“…We = 0.68, 0.85 GHz for [17], and = 0.9, 1.8, 2.45 GHz for [38]. It can be shown that this ratio is approximately independent of and only dependent of and .…”
Section: Joint Model Of Input Power and Operating Frequencymentioning
confidence: 86%
See 1 more Smart Citation
“…We = 0.68, 0.85 GHz for [17], and = 0.9, 1.8, 2.45 GHz for [38]. It can be shown that this ratio is approximately independent of and only dependent of and .…”
Section: Joint Model Of Input Power and Operating Frequencymentioning
confidence: 86%
“…The results in [10], [17], [38]- [41] provide the conversion efficiency versus frequency at different input power levels and the conversion efficiency versus input power at different frequencies. This gives…”
Section: Joint Model Of Input Power and Operating Frequencymentioning
confidence: 99%
“…The maximum conversion efficiency was 67.4% for the GSM-1800 frequency band and input power of −3 dBm. The authors in [ 25 ] presented a triple-band rectifier that was operating in the frequency bands of GSM-900, GSM-1800, and Wi-Fi 2.4 GHz. They reported a measured RF-to-DC conversion efficiency of 52% for an input power of 0 dBm and the frequency band of GSM-900.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][7][8][9][10][11][12][13] Several single band structures for ambient energy harvesting are presented in. 14,15 Thedual-band, 13,16,17 triple-band, 7,18,19 or quad-band 20 rectenna are some methods to improve the amount of energy harvested. To obtain a multi-band rectenna, all sections of the rectenna must be multi-band.…”
Section: Introductionmentioning
confidence: 99%